Implementasi Integrasi Twin Towers Dalam Materi Model Kurikulum Pendidikan Inklusif Pada Mata Kuliah Pendidikan Inklusif Prodi S1 PGMI Universitas Islam Negeri Sunan Ampel Surabaya - Rahmat Rudianto (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This community service program aimed to implement the Twin Towers Integration paradigm in the inclusive education curriculum model within the Inclusive Education course of the PGMI undergraduate program at UIN Sunan Ampel Surabaya. The program was conducted by doctoral students (S3 PGMI) through academic mentoring for third-semester undergraduate students as a form of community service in the academic context. A participatory-educative approach integrated with classroom instruction was employed, including needs analysis, concept socialization, curriculum development training, and evaluation. The results indicate a significant improvement in students’ conceptual understanding of inclusive education integrated with Islamic values such as compassion, justice, and respect for diversity. Students also demonstrated more open and reflective attitudes toward learner diversity. In terms of practical skills, they were able to design inclusive curricula by applying adaptation models of duplication, modification, substitution, and omission based on the context of Islamic elementary schools. These findings confirm that the Twin Towers Integration paradigm is effective in strengthening prospective teachers’ competencies theoretically, affectively, and practically.